Potato innovation to increase sale value into fried potato with sambal and innovation into a moisturizer product for skin health in Geucue Menara Village, Banda Aceh City (Inovasi kentang untuk peningkatan nilai jual menjadi sambal goreng dan inovasi kentang menjadi produk pelembab untuk kesehatan kulit di Gampong Geucue Menara, Kota Banda Aceh) - Lestari, Wahyu; Meutia, Rita; Suryani, Ade Irma; Saputra, Mulia (Universitas Syiah Kuala, 2023)
Potatoes are one of the food crops that most widely consumed as a source of energy. Processed potato foods vary greatly, one of which is fried potato sambal. The aim of this Community Service (PkM) is to provide product innovation to business owners so that they can increase the income of the owner of the fried potato sambal business. The place where this community service is carried out is at the Fried Potato Sambal Production House in Geuceu Menara Village, Jaya Baru Subdistrict, Banda Aceh. This production house usually uses red potatoes as the main raw material. In this PkM activities, potato skins, which are usually waste, will be innovated into moisturizing products for the skin. There are two types of potatoes used in this PkM activities, namely yellow potatoes and red potatoes. Both of the potatoes were peeled, those peel were extracted and then these two extracts will be used as the main ingredients in making moisturizer products. Antioxidant activity was also determined using the DPPH method. The results obtained were that the extracts of both types of potato skin had antioxidant activity with IC50 values of 5.10 (yellow potato skin) and 11.32 (red potato skin). In conclusion, yellow potato skin extract and red potato skin extract have strong antioxidant activity so that they can be used as a good moisturizer product.